What makes a great exhibition? - Marincola, Paula; Philadelphia Exhibitions Initiative (Philadelphia, PA : Philadelphia Exhibitions Initiative, Philadelphia Center for Arts and Heritage ; Chicago, IL : Distributed for Reaktion Books in the USA and Canada by the University of Chicago Press, 2006)
- Introduction : Practice makes perfect / Paula Marincola##- Show and tell / Robert Storr##- In lieu of higher ground / Lynne Cooke##- You talking to me? On curating group shows that give you a chance to join the group / Ralph Rugoff##- The unstable institution / Carlos Basualdo##- With our faces to the rising sun / Thelma Golden with Glenn Ligon##- Mies's new national gallery : empty and full / Detlef Mertins##- Design and architecture / Paola Antonelli interviewed by Bennett Simpson##- Who's afraid of gift-wrapped kazoos? / Jeffrey Kipnis##- Handy-crafts : a doctrine / Glenn Adamson##- Temple/White cube/Laboratory / Iwona Blazwick##- Making space for art / Mary Jane Jacob##- Questions of practice / Mark Nash##- Wall text / Ingrid Schaffner.
CCS Gent
Includes index.
boek